Coffee Farmers Empowerment by LMDH Argo Mulyo in Tambi Village, Kejajar District, Wonosobo Regency - Yuni Indarti (Prospect Publishing, 2022)
Empowerment is an effort made by the community, with or without the support of outsiders to improve their lives based on their own power, through power optimization efforts, as well as increasing their bargaining position, in other words, empowerment must put the strength of the community as the main capital and avoid the